Effects of Ginger Brown Sugar Decoction on Reducing Primary Dysmenorrhea Pain with Yang Deficiency Syndrome - Setiyawati, Erna; Nando, Aryaprana; Khuril R, Muslihatin; Anwar, Laode Muhamad; Xaverius , Franciscus (Green Publisher Indonesia, 2025)
Menstrual pain (dysmenorrhea) affects approximately 45–95% of women of reproductive age in Indonesia and may interfere with daily activities. Dysmenorrhea is a gynecological disorder caused by an imbalance of progesterone in the blood, leading to pain. In Traditional Chinese Medicine (TCM), dysmenorrhea is referred to as tongjing and is often associated with yang deficiency syndrome. Ginger and palm sugar decoction has natural warming, anti-inflammatory, and analgesic effects, making it suitable for treating cold-type menstrual pain based on TCM principles. Objective: To determine the effect of ginger and palm sugar decoction on reducing primary dysmenorrhea in adolescents with yang deficiency syndrome. Methods: A quantitative study using a single-group pretest-posttest design without a control group. A total of 20 adolescent girls aged 10–18 were given the decoction three times a day for two days. The study was conducted at Mitshaqul Ummah Islamic Boarding School, Cianjur Regency. Results: The average pain score decreased from 4.10 to 1.75 after intervention. The Paired Sample T-Test showed a t-value of 14.104 (df = 19) with a significance level of p < 0.001, indicating a statistically significant reduction in pain. A 50% decrease was also found in seven key indicators of yang deficiency symptoms, based on a TCM physical constitution questionnaire. Conclusion: Ginger and palm sugar decoction significantly reduces the severity of primary dysmenorrhea and alleviates symptoms of yang deficiency. These findings are consistent with TCM principles, which emphasize warming the body and strengthening yang energy to relieve pain.